Analisis Laporan Keuangan Pemerintahan dalam Kondisi Norma - , Siti Muslihah ([Yogyakarta] : Universitas Gadjah Mada, 2012)
One of reason for the importance of this study is the fact that public decisionmaking, especially economic policy still lead to poor decisions. This study aims to determine whether govermental financial statement analysis can yield information on which to base public decisions, especially economic policy. In addition, this study also attempted to prove the government's financial statement analysis techniques which can yield information on which to base public decisions, especially economic policy. Based on the review of concepts and techniques of financial statement analysis and benchmarking against the concept of governance and financial statement analysis techniques in the business sector, financial statement analysis showed that the government is able to produce information on which to base public decisions, especially economic policy. Apparently until recently, Flow of Funds is the government's financial statements that meet the needs of financial statement analysis of government that is able to produce information on which to base public decisions, especially economic policy. This study takes the period 2001-2005 as a period of study, i.e., when the United States under normal conditions. Simulations performed on the financial statements of government and the United States Flow of Funds. Simulations performed to see Funds Flow analysis capabilities in generating information on which to base public decisions, especially economic policy. The simulation results are then described show that the analysis of Fund Balance capable of describing the condition, performance, and resource capacity of government and all stakeholders so as to produce information on which to base public decisionmaking especially economic policy under normal conditions.